Spizhavka N. V. Conventional metaphors of the emotional concept anger (on the material of the contemporary English fiction) - Spizhavka N. V. (Philological Treatises, 2020)
The article establishes correlates of the ANGER conceptual referent, which constitute the image content of the emotional concept ANGER in the contemporary English fiction. Basic correlates of the ANGER conceptual referent include the concepts NATURAL PHENOMENA, LIQUID, ANIMAL.